Surfacing : on being Black and feminist in South Africa - Lewis, Desiree; Baderoon, Gabeba (Johannesburg : Wits University Press, 2021)
What do African feminist traditions that exist outside the canon look and feel like? What complex cultural logics are at work outside the centres of power? How do spirituality and feminism influence each other? What are the histories and experiences of queer Africans? What imaginative forms can feminist activism take? Surfacing: On Being Black and Feminist in South Africa is the first collection of essays dedicated to contemporary Black South African feminist perspectives. Leading feminist theorist, Desiree Lewis, and poet and feminist scholar, Gabeba Baderoon, have curated contributions by some of the finest writers and thought leaders. Radical polemic sits side by side with personal essays, and critical theory coexists with rich and stirring life histories. By including writings by Patricia McFadden, Panashe Chigumadzi, Sisonke Msimang, Zukiswa Wanner, Yewande Omotoso, Zoë Wicomb and Pumla Dineo Gqola alongside emerging thinkers, activists and creative practitioners, the collection demonstrates a dazzling range of feminist voices. The writers in these pages use creative expression, photography and poetry in eclectic, interdisciplinary ways to unearth and interrogate representations of Blackness, sexuality, girlhood, history, divinity, and other themes. Surfacing is indispensable to anyone interested in feminism from Africa which, the contributors show, is in vivid and challenging conversations with the rest of the world.
Introduction: Being Black and Feminist / Desiree Lewis and Gabeba Baderoon -- Winnie Mandela and the Archive: Reflections on Feminist Biography / Sisonke Msimang -- Representing Sara Baartman in the New Millennium / Zoë Wicomb and Desiree Lewis -- PART I UNMAKING -- a playful but also very serious love letter to gabrielle goliath / Pumla Dineo Gqola -- Teaching Black, Teaching Gender, Teaching Feminism / Mary Hames -- Querying the Queer / gertrude fester-wicomb -- South African Feminists in Search of the Sacred / Fatima Seedat -- 'Who Do You Think You Are to Speak to Me Like That?' / jackï job -- Refining Islamic Feminisms: Gender, Subjectivity and the Divine Feminine / Sa'diyya Shaikh -- Black Lesbian Feminist Thoughts of a Born Queer / Zethu Matebeni -- Conversations about Photography with Keorapetse Mosimane, Thania Petersen and Tshepiso Mazibuko / Ingrid Masondo -- PART II POSITIONING -- What We Make to Unmake: The Imagination in Feminist Struggles / Yewande Omotoso -- Breathing Under Water / Danai S. Mupotsa -- 'Do I Make You Uncomfortable?' Writing, Editing and Publishing Black in a White Industry / Zukiswa Wanner -- Echoes of Miriam Tlali / Barbara Boswell -- My Two Husbands / Grace A. Musila -- Hearing the Silence / Panashe Chigumadzi -- PART III REMAKING -- Thinking through Transnational Feminist Solidarities / Leigh-Ann Naidoo -- The Music of My Orgasm / Makhosazana Xaba -- Bringing Water to Krotoa's Gardens: Decolonisation as Direct Action / Yvette Abrahams -- Living a Radical African Feminist Life: A Journey to Sufficiency Through Contemporarity / Patricia McFadden
Includes bibliographical references (pages 323-326) and index.
JSTOR
Keywords: Women, Black -- South Africa; Feminism -- South Africa; Femmes noires -- Afrique du Sud; Féminisme -- Afrique du Sud; Feminism; Women, Black; South Africa; Feminisme -- Afrique du Sud; Noires -- Afrique du Sud